Media Pembelajaran Animasi Shot Size Sinematografi Berbasis Motion Graphic Pada Program Studi TIMD Jurusan Teknik Komputer Politeknik Negeri Sriwijaya - Ikhthison Mekongga; Santi Sasmitha; Hartati Deviana; Ali Firdaus (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract— The library is one of the sources of information and a place to learn so that any information on borrowing books is stored by the library and will produce data on borrowing books in large sizes. The Abdi Nusa Stikes Library has a total number of 1.535 books. And the book borrowing data at the Abdi Nusa Stikes library for the past 2 years, namely 2016-2017, there are 1,610 borrowers, so it will affect the preparation of the book lending pattern, and besides that the book layout has not well recommended so that visitors find it difficult to find books that are often borrowed. So to overcome this problem the author will look for patterns of borrowing books that are often borrowed simultaneously using the Association rule method. The author will also perform a comparative analysis of the two algorithms used, namely the Apriori algorithm and the ECLAT algorithm. The author has also set a minimum support value of 0.008 and a minimum confidence of So that the book borrowing data in 2016 and 2017 using the Apriori algorithm and the Eclat Algorithm produce the same rule, namely in 2016 forming 1 rule and 2017 forming 2 rules so that from the formation of the two algorithms it can be seen that the ECLAT algorithm is superior to the Apriori algorithm seen from the value support both Keywords— Libraries, Association Rule, Apriori Algorithm, ECLAT Algorithm